Determinan Perilaku Suami yang Mempengaruhi Pilihan Penolong Persalinan bagi Istri - Sodikin Ova Emilia, Koentjoro (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
Background: Culture often gives limitation for women in decision taking regarding their health. In fact, husbands play an absolute role to determine who will attend and help the delivery.Objective: To explore husbands’ behavior in choosing and determining that will help their wife’s delivery.Methods: This is a survey study using cross-sectional design. The samples were 110 husbands who had a wife delivering in Pekuncen Sub District’s primary health center, Banyumas District, Central Java, during the period of 1 January 2005 – 31 December 2005.Results: The variables that had significant relationship in choosing and determining birth attendant were husbands’ education OR = 7.57 (95% Cl: 2.11 – 27.15), delivery cost OR = 6.77 (95% Cl: 2.06 – 22.28) and husbands’ trust OR = 0.15 (95% Cl: 0.04 – 0.55). Husbands with higher level of education had an opportunity of 7.5 times increased to choose and determine the birth attendant compared to those with lower lever of education. Husbands’ trust had an opportunity of 7 times decreased to choose and determine the birth attendant compared to those with no trust to the birth attendant. Expensive delivery cost would be 6.7 times increased the determination of the birth attendant by health provider compared to cheap delivery cost. It was because of some additional cost for the health provider that was relatively high. As a result, mean distribution curve of the birth attendant cost would tend to go to the right.Conclusions: Husbands’ education, cost, and trust factors were the determinant factors in choosing and determining who would attend the delivery.Keywords: health reproduction, husband, determining of child-birth assistant